The Over-the-Hill Gang rides again - McCowan, George, 1927-1995; Brennan, Walter, 1894-1974; Thomas-Spelling Productions; Cinetel Films ([Los Angeles, CA] : Thomas/Spelling Productions Inc., 1970)
Walter Brennan is back as the clever and funny over the hill Texas Ranger Nash Crawford. This time the gang must face corruption in their own home town. The gang put their heads together to clean up their town, take back the rule of law and rehabilitate the town lush along with way. --
Originally broadcast on ABC.
Walter Brennan, Edgar Buchanan, Andy Devine, Chill Wills, Fred Astaire, Paul Richards.
Cinematographer, Fleet Southcott III; editor, Richard Farrell; music, David Raksin.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 14, 2015).
Keywords: Texas Rangers -- Drama; Corruption -- Drama; Western films; Western television programs; Made-for-TV movies; Internet videos; Streaming video